북한이탈주민의 식사의 질 평가: 성인 영양지수를 기반으로 - 권새별(SaeByeol Kwon); 김경남(Kyoung-Nam Kim); 신문경(Moon-Kyung Shin) (Journal of nutrition and health, 2023)
Purpose: The purpose of this study was to assess the diet intake status and quality of adults from North Korea who had lived in Seoul and Gyeonggi-do, using the nutrition quotient (NQ) for Korean adults. Methods: A number of 166 adults aged from 20 to 64 years were enrolled as study subjects. A structured questionnaire was used to collect information on their demographic characteristics, food consumption frequency, eating behaviors, and NQ. The NQ score was then used to measure the overall diet quality. The NQ score was composed of four major age-based categories. 'Balance', 'Diversity', 'Moderation', and 'Dietary behavior' were utilized as scores for measurements within each of the four categories. The scores for all four categories were summed up, resulting in the total NQ score. Participants' age groups were stratified by 20's, 30's, 40', and over 50's. A χ2 test and generalized linear regression (GLM) model were used to assess a significance for difference of subject distribution in categorical and continuous variables in the food consumption frequency, eating behaviors, and NQ scores. Results: Participants in younger age groups were more likely to report consumption of ramyeon, fast food, sweet and greasy baked products, processed beverage, delivery food, and night snacks than the older age groups. Most importantly, participants in 20's age group were less likely to report the total NQ and moderation score than the 50's age group. Conclusion: In this study, the 20's age group displayed a lower NQ characteristic for an unbalanced diet. Therefore, it is imperative for adults from North Korea to be given individualized diet instructions along with nutritional education programs. 본 연구는 성인영양지수 조사지를 바탕으로 북한이탈주민의 전반적인 식사의 질을 평가하고자 진행되었다. 특히 연령대별 식품 섭취 빈도와 식습관 및 식행동, 영양 지수의 차이를 분석하였다. 대상자는 서울 및 경기 일부 지역의 만 19-64세 성인 166명을 대상으로 진행되었으며 각 연령대별로 20대 41명, 30대 41명, 40대 41명, 50대이상 43명으로 연령대를 평준화하였다. 연령대가 낮을수록 라면, 패스트푸드, 과자 (초콜릿, 사탕 포함), 달거나 기름진 빵 (케이크, 도넛, 단팥빵 등), 가당 음료 등 고에너지 식품 섭취 빈도와 외식, 야식 섭취 비율이 높은 것으로 나타났다. 또한 20대 연령대에서 총점 NQ, 절제 영역 총 점수가 낮고 등급은 '하'로 판정된 비율이 높았다. 50대 연령대에서 절제영역의 점수가 높게 나타난 원인은 라면, 패스트푸드, 과자, 달거나 기름진 빵, 가당 음료 등과 같은 고에너지 식품 섭취 빈도도 낮기 때문인데, 이는 이 집단이 절제력있는 식사를 하고 있는 것으로 비춰질 수도 있으나 중년층에서 패스트푸드, 라면과 같은 식품의 기호도가 낮아 아예 섭취 고려 대상이 아니라는 점에 주목해야 한다. 본 연구에서 주목해야 할 점은 연령이 낮을수록 식사의 질이 매우 열악하게 나타나 식사의 질 개선을 위한 맞춤형 영양 교육 프로그램 개발 및 보급의 필요성을 시사한다. 이에 본 연구의 결과와 시사점이 북한이탈주민의 건강 증진을 위한 영양 교육과 이를 위한 정책 마련의 기초자료로 활용되기를 기대한다.